2020
DOI: 10.1017/ice.2019.303
|View full text |Cite
|
Sign up to set email alerts
|

Pathogens causing central-line–associated bloodstream infections in acute-care hospitals—United States, 2011–2017

Abstract: Objective:To describe pathogen distribution and rates for central-line–associated bloodstream infections (CLABSIs) from different acute-care locations during 2011–2017 to inform prevention efforts.Methods:CLABSI data from the Centers for Disease Control and Prevention (CDC) National Healthcare Safety Network (NHSN) were analyzed. Percentages and pooled mean incidence density rates were calculated for a variety of pathogens and stratified by acute-care location groups (adult intensive care units [ICUs], pediatr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 29 publications
2
32
0
Order By: Relevance
“…In contrast, in the Safdar's study, 87% of microorganisms identified were CoNS. In this context, and consistently with our findings, a change in the epidemiology of intravascular catheter infection toward lower prevalence of CoNS and increasing proportion of Gram-negative microorganisms has been documented in several recent studies [12,13,35]. In light of these considerations, the description of this cohort may probably better represent this issue.…”
Section: Discussionsupporting
confidence: 88%
“…In contrast, in the Safdar's study, 87% of microorganisms identified were CoNS. In this context, and consistently with our findings, a change in the epidemiology of intravascular catheter infection toward lower prevalence of CoNS and increasing proportion of Gram-negative microorganisms has been documented in several recent studies [12,13,35]. In light of these considerations, the description of this cohort may probably better represent this issue.…”
Section: Discussionsupporting
confidence: 88%
“…Enterococcus faecium is commonly inhabiting the gut of animals and humans but has also emerged as a nosocomial pathogen causing a sizable fraction of healthcareassociated infections, specifically device-associated infections like central line-associated bloodstream and surgical site infections [1,2]. The intrinsic and acquired multi-drug resistance against fluoroquinolones, aminoglycosides, and more importantly against glycopeptides motivated the inclusion of E. faecium in the WHO global priority list [3].…”
Section: Introductionmentioning
confidence: 99%
“…Yeast-related BSI are usually healthcare-associated infections with a high mortality of up to 60% in critically ill patients [ 1 , 3 5 ]. Importantly, BSI caused by Candida spp., central-line-associated BSI in particular, have been increasing over the past decades [ 6 ]. The international EPIC II study including more than 14,000 patients showed that Candida was the third most common cause of infection and was second in both North America and Western Europe [ 7 ].…”
Section: Introductionmentioning
confidence: 99%